Lysophosphatidic Acid May Be a Novel Biomarker for Early Acute Aortic Dissection - Pan, Xiaogao; Zhou, Yang; Yang, Guifang; He, Zhibiao; Zhang, Hongliang; Peng, Zhenyu; Peng, Wen; Guo, Tuo; Zeng, Mengping; Ding, Ning; Chai, Xiangping (Frontiers in Surgery, 2022)
Background: Misdiagnosis and delayed diagnosis of acute aortic dissection (AAD) significantly increase mortality. Lysophosphatidic acid (LPA) is a biomarker related to coagulation cascade and cardiovascular-injury. The extent of LPA elevation in AAD and whether it can discriminate sudden-onset of acute chest pain are currently unclear. Methods: We measured the plasma concentration of LPA in a cohort of 174 patients with suspected AAD chest pain and 30 healthy participants. Measures to discriminate AAD from other acute-onset thoracalgia were compared and calculated. Results: LPA was significantly higher in AAD than in the AMI, PE, and the healthy (344.69±59.99 vs. 286.79±43.01 vs. 286.61±43.32 vs. 96.08±11.93, P<0.01) within 48 hours of symptom onset. LPA level peaked at 12 hours after symptom onset, then gradually decreased from 12 to 48 hours in AAD. LPA had an AUC of 0.85 (0.80-0.90), diagnosis threshold of 298.98mg/dl, a sensitivity of 0.81, specificity of 0.77, and the negative predictive value of 0.85. The ROC curve of LPA is better than D-dimer (P=0.041, Delong test). The decision curve showed that LPA had excellent standardized net benefits. Conclusion: LPA showed superior overall diagnostic performance to D-dimer in early AAD diagnosis may be a potential biomarker, but additional studies are needed to determine the rapid and cost-effective diagnostic tests in the emergency department.